2010
DOI: 10.1111/j.1365-2893.2010.01401.x
|View full text |Cite
|
Sign up to set email alerts
|

Is chronic hepatitis B being undertreated in the United States?

Abstract: Chronic infection with the hepatitis B virus (HBV) is a major risk factor for development of end-stage liver disease, including cirrhosis, liver failure and primary liver cancer. There are now seven antiviral agents approved by the United States Food and Drug Administration (FDA) for the management of chronic HBV infection. Despite the fact that there are between 1.4 and 2 million chronic HBV infections in the United States, fewer than 50,000 people per year receive prescriptions for HBV antiviral medications.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
139
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(143 citation statements)
references
References 40 publications
3
139
1
Order By: Relevance
“…3 A low diagnosis rate and poor access to clinical care among people with CHB is a major barrier to reducing hepatitis B-related morbidity and mortality. It is estimated that only 56% of people with CHB in Australia 4 and less than 40% in the United States 5 have been diagnosed, while approximately 13% 6 and 50% 5 of those who have been diagnosed receive clinical care for their infection in these two countries, respectively. The proportion of untreated people with CHB in Europe ranges between 37% and 66%.…”
mentioning
confidence: 99%
“…3 A low diagnosis rate and poor access to clinical care among people with CHB is a major barrier to reducing hepatitis B-related morbidity and mortality. It is estimated that only 56% of people with CHB in Australia 4 and less than 40% in the United States 5 have been diagnosed, while approximately 13% 6 and 50% 5 of those who have been diagnosed receive clinical care for their infection in these two countries, respectively. The proportion of untreated people with CHB in Europe ranges between 37% and 66%.…”
mentioning
confidence: 99%
“…These patients have a 15 to 25% greater risk of developing serious sequelae, such as hepatocellular carcinoma, eventually resulting in death (1). Currently approved treatments for chronic hepatitis B virus infection consist of either nucleos(t)ide analogues (NAs), which are well tolerated but usually have to be taken lifelong, or 48 weeks of pegylated interferon, which is associated with significant side effects (2).…”
mentioning
confidence: 99%
“…Currently approved treatments for chronic hepatitis B virus infection consist of either nucleos(t)ide analogues (NAs), which are well tolerated but usually have to be taken lifelong, or 48 weeks of pegylated interferon, which is associated with significant side effects (2). Only a small subset of chronic hepatitis B patients are treated today (4 to 5% in the United States), and only 5 to 10% achieve immune control of infection (i.e., functional cure), as indicated by hepatitis B surface antigen (HBsAg) loss with or without HBsAg seroconversion (1,3). Therefore, the development of novel antivirals with different modes of action and fewer side effects is highly desired since the use of such drugs, alone or in combination, may shorten the treatment duration and increase cure rates.…”
mentioning
confidence: 99%
“…[20][21][22][23][24] It is also noteworthy that 19 (1.6%) of our 1214 subjects were found to be coinfected with HCV (i.e., positive for anti-HCV and HCV RNA), another major risk factor for chronic liver disease. A study in a US National Veterans cohort showed that chronic HCV carriers with documented HBV viremia were at significantly higher risk for cirrhosis compared to those with HBV monoinfection.…”
Section: Discussionmentioning
confidence: 99%